What does corporate social advocacy signal? Evidence from boycott participation decisions - Pyemo N. Afego; Imhotep P. Alagidede (Journal of Capital Markets Studies, 2021)
Purpose - This paper explores how a firm's public stand on a social-political issue can be a salient signal of the firm's values, identity and reputation. In particular, it investigates how boycott participation-conceptualized as a cue of a corporation's stand on important social-political issues-may affect the stock market valuation of that corporation, as well as how corporations legitimise their stand on the issues. Design/methodology/approach - The authors employ a mixed-methods design that uses both qualitative techniques (content analysis) and quantitative methods (event study methodology) to examine a sample of US firms who participated in a boycott campaign that sought to call attention to issues of hate speech, misinformation and discriminatory content on social media platform Facebook. Findings - Findings from the qualitative content analysis of company statements show that firms legitimise their stand on, and participation in, the boycott by expressing altruistic values and suggesting to stakeholders that their stand aligns not only with organizational values/convictions but also with the greater social good. Importantly, the event study results show that firms who publicly announced their intention to participate in the boycott, on average, earn a statistically significant positive abnormal stock return of 2.68% in the four days immediately after their announcements. Research limitations/implications - Findings relate to a specific case of a boycott campaign. Also, the sample size is limited and restricted to US stocks. The signalling value of corporate social advocacy actions may vary across countries due to institutional and cultural differences. Market reaction may also be different for issues that are more charged than the ones examined in this study. Therefore, future research might investigate other markets, use larger sample sizes and consider a broader range of social-political issues. Practical implications - The presence of significant stock price changes for firms that publicly announced their decision to side with activists on the issue of hate propaganda and misinformation offers potentially valuable insights on the timing of trades for investors and arbitrageurs. Insights from the study also provide a practical resource that can be used to inform organizations' decision-making about such issues. Social implications - Taking the lead to push on social-political issues, such as hate propaganda, discrimination, among others, and communicating their stands in a way that speaks to their values and identity, could be rewarding for companies. Originality/value - This study provides novel evidence on the impact that corporate stances on important social-political issues can have on stock market valuation of firms and therefore extends the existing related research which until now has focused on the impact on consumer purchasing intent and brand loyalty.
Keywords: G10; G14; M14; 330; Abnormal return; Content analysis; Event study; Boycotts; Corporate social advocacy; Signalling effect